2022
DOI: 10.1017/jmo.2022.38
|View full text |Cite
|
Sign up to set email alerts
|

Business, pleasure or both?: motivations and changing motivation of self-initiated expatriates

Abstract: Responding to calls for more knowledge about the motivations (and changing motivations) of self-initiated expatriates (SIEs), this qualitative research examines 58 Australian SIEs working in culturally (dis)similar host contexts, to address the question: Why are Australian SIEs motivated to expatriate to South Korea or the United Kingdom? The findings demonstrate that, although personal/lifestyle considerations are important to SIEs, career-related considerations are either primary or become more prevalent fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Their importance highly depends on many factors, such as country context, gender, mobility frequency (Thorn, 2009), demographic characteristics, and industry or sector (Suutari et al ., 2018). Additionally, they change throughout the expatriation experience (Despotovic et al ., 2022), even for repatriation decisions (Tharenou and Caulfield, 2010). For example, it was found that disregard demographic factors, the desire for adventure and personal-lifestyle goals consistently rated as the most influential on SIEs decisions (Doherty et al ., 2011; Richardson and Mallon, 2005; Richardson and McKenna, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Their importance highly depends on many factors, such as country context, gender, mobility frequency (Thorn, 2009), demographic characteristics, and industry or sector (Suutari et al ., 2018). Additionally, they change throughout the expatriation experience (Despotovic et al ., 2022), even for repatriation decisions (Tharenou and Caulfield, 2010). For example, it was found that disregard demographic factors, the desire for adventure and personal-lifestyle goals consistently rated as the most influential on SIEs decisions (Doherty et al ., 2011; Richardson and Mallon, 2005; Richardson and McKenna, 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some SIEs relocated to a particular country to reconnect with their loved ones, acquaintances or due to personal reasons such as a family-related interests (Muir et al ., 2014; Oberholster et al ., 2013; Tharenou and Caulfield, 2010). Others are motivated by the idea of living abroad and finding a better quality of life (Despotovic et al ., 2022; Doherty, 2013), while some SIEs purposefully avoid culturally challenging locations (Doherty et al ., 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) The analysis of careers of self-initiated expatriates (SIEs) has received little attention so far. Research on SIEs has focused on a variety of topics, such as cultural adjustment (e.g., Kumra et al, 2021), gender issues (Haak-Saheem et al, 2022), repatriation (Andresen, 2021), motives (Despotovic et al, 2022), and outcomes (e.g., Maharjan et al, 2021). However, the overall results regarding international careers remain unclear, making it difficult to draw general conclusions.…”
Section: Originality and Innovative Aspects Of The Glomo Projectmentioning
confidence: 99%